A Novel Percutaneous Technique to Implant Plate-Type Electrodes - Logé, D.; De Coster, O.; Pollet, W.; Vancamp, T. (min - Minimally Invasive Neurosurgery, 2011)
In spinal cord stimulation (SCS) mainly 2 distinctive implantation techniques can be recognized: the percutaneous and surgical technique.A puncture is made with a blunt 14 gauge Tuohy needle. Once inside the epidural space the guide wire needs to be advanced in the epidural space, then the Tuohy needle is removed. The Epiducer is advanced under the guidance of lateral fluoroscopy, to confirm epidural entry. The S-series electrode is introduced through the sheet in the epidural space.We present a novel technique to introduce small profile paddle leads (S-SeriesTM: St. Jude Medical – Neuromodulation Division, Plano, TX) in the epidural space via a percutaneous approach using the EpiducerTM (St. Jude Medical – Neuromodulation Division, Plano, TX) lead delivery system.
Keywords: SCS; percutaneous access; plate electrode; EpiducerTM; perc-paddle lead